Fearful dogs have increased plasma glutamine and γ-glutamyl glutamine - Jenni Puurunen (Nature Portfolio, 2018)
Abstract Anxiety-related disorders, including fearfulness are common and leading welfare problems among the worldwide dog population. The etiology of anxieties is complex and affected by genetic and environmental factors. Thus, there is a need for more comprehensive approaches, such as metabolomics, to understand the causes of anxiety and to identify anxiety-related biomarkers for more efficient diagnostic and treatment options. To study metabolic alterations related to canine fearfulness, a non-targeted plasma metabolite profiling was performed in a cohort of 20 fearful and 21 non-fearful dogs. The results showed that nine metabolic features were significantly associated with fearfulness. The most prominent change included increased plasma glutamine and γ-glutamyl glutamine (γ-Glu Gln) in fearful dogs across breeds. Alterations in glutamine metabolism have previously been associated with several psychiatric disorders, indicating the relevance of this finding also in dogs. In addition, we describe a novel breed-specific association between renal biomarker symmetric dimethylarginine (SDMA) and canine fearfulness. These observed metabolic alterations may result from high levels of prolonged psychological stress in fearful dogs.